Design of two-stage CMOS amplifier for quartz crystal resonator - Mohd Taufik, Muhammad Syamsi; Nordin, Anis Nurashikin; Khan, Sheroz; Zainuddin, Ahmad Anwar (2013)
Quartz crystal oscillators is widely used in many types of electronics equipment for our daily life applications such as mobile communication, military, industrial measurement, an others due to its high stability clock sources. In this paper, a Two-Stage CMOS op-amp for a quartz crystal-based oscillator is presented. The design of two-stage CMOS op amp is critically discussed. Two-stage CMOS op amp is consist of two stages. Each stage can be designed with various amplifier topologies. The first stage is differential amplifier. The second stage of twostage op amp is a common-source amplifier. The op amp achieves a gain of 6.134 dB at VDD of 3.3 V and VSS of -3.3 V. The twostage CMOS op amp is combined with 10 MHz quartz crystal resonator to create an oscillator at the frequency of ~10MHz. The gain of 13.32dB is achieved. This oscillator is simulated using Cadence in MIMOS 0.35 um CMOS process.